JAMINAN KERAHASIAAN INFORMASI PAJAK TERHADAP PROPERTI PEMBAYARAN PAJAK DALAM PEMERIKSAAN MANAJEMEN DAN TANGGUNG JAWAB KEUANGAN NEGARA YANG DILAKUKAN DEWAN AUDIT - Johannes Johny Koynja (Faculty of Law, University of Mataram, 2017)
This research analysis meant to find out legal consideration used byConstitution judge, whether in accordance or not to legal principles, moral andsocial justice. Therefore,this article tend to place problems that linked to conflict of norm in term of The Audit Board (BPK) authorities over a good and compliance Taxpayerl,and progressive related The Constitutional Court decision of The Audit Board(BPK) authorities of a good and compliance taxpayer in the context of The 1945Constitution of The Republic of Indonesia at its proportion in order tostraightening the consistency of rule of law in Indonesia’s legal system, for theshake of completion of logical degree of optimal norm.Intrinsically, decision in the case of petition for Judicial Review of the Act Number 28 of 2007 on the Third Amendment to the Act Number 6 of 1983 on the General Taxation Provisions and Procedures against the 1945 Constitution of the Republic of Indonesia, can be made guidance (stelling) to the happening ofopaqueness norm or obscurity norm (vague van normen) which flange at thehappening conflict of norm (geschiljd van normen) related existence of twoimportance of law between The Audit Board (BPK) and Taxpayers which both ofthe same owning of rights which under the aegis of Constitution.